PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA (Studi Kasus di PT Mutiara Nusantara Globalindo) - FX. Pudjo Wibowo; Sugandha Sugandha; Fidellis Wato Tholok (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
The purpose of this paper is to determine the effect of organizational culture and work environment on performance at PT Mutiara Nusantara Globalindo. In this study, research was conducted on 100 respondents of PT Mutiara Nusantara Globalindo's employees, through questionnaires. The method used in this research is descriptive and qualitative methods. Based on the answers to the questionnaire, raw data have been obtained which are then processed using SPSS version 25 so that it becomes useful data for this study. Organizational culture variables (X1) and work environment partially have a positive and significant effect (t count of organizational culture 12,592 > T table 1,984 and 0,000 <0,05) and (t count value of 2,820 work environment > t table 1,084 and 0,006 <0,05) on the performance of PT Mutiara Nusantara Globalindo while the organizational culture variable (X1) and the work environment together have a positive and significant influence F count of 260,865 with a significance value of 0,000 so that the calculated F value > F table or 260,865 > 2.46 or the level of significance (sig) 0,000 <0,05, on the performance of PT Mutiara Nusantara Globalindo and adjusted R2 Value shows that organizational culture and work environment contributed 84% to the performance of PT Mutiara Nusantara Globalindo while 16% was explained by other reasons.